2019
DOI: 10.1017/s0007114519001892
|View full text |Cite
|
Sign up to set email alerts
|

Street food in Dushanbe, Tajikistan: availability and nutritional value

Abstract: Street food is part of the culture in central Asia. Although nourishing food can be found, unhealthier options are becoming increasingly popular – a marker of nutrition transition. The nutritional composition of street food in urban settings is, however, unknown. The objective of the present study was, thus, to characterise the street food availability in Dushanbe, Tajikistan. A total of 800 street food vending sites in public markets were selected through random and systematic procedures. Trained interviewers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 23 publications
(34 reference statements)
8
28
1
Order By: Relevance
“…Of the 30 street foods whose nutritional composition was analyzed in this study, the homemade foods had larger servings sizes and also energy content per serving, resembling the results found in Dushanbe, Tajikistan, a neighboring country (Albuquerque et al., 2019). A single serving of some of the homemade dishes accounted for a large share of energy, almost half of the daily recommendation for an average adult (e.g., manty and lagman ), and macronutrients.…”
Section: Discussionsupporting
confidence: 73%
“…Of the 30 street foods whose nutritional composition was analyzed in this study, the homemade foods had larger servings sizes and also energy content per serving, resembling the results found in Dushanbe, Tajikistan, a neighboring country (Albuquerque et al., 2019). A single serving of some of the homemade dishes accounted for a large share of energy, almost half of the daily recommendation for an average adult (e.g., manty and lagman ), and macronutrients.…”
Section: Discussionsupporting
confidence: 73%
“…Home-made and industrial foods were found to have medium (12•6 kJ/g) and high (18•0 kJ/g) mean energy density, respectively (29) , which corroborates previous findings that street foods are energy-dense sources of nutrients for populations worldwide (10) . Industrial wafers and biscuits presented the highest energy density (approximately 20•9 kJ/g), possibly reflecting a high sugar and fat content (30) , as previously observed in samples of street food in Dushanbe, Tajikistan (26) . Although the free sugar content was not discriminated in this study, they may have a high sugar content, which is line with existing literature on street food composition (10,25,26,31) .…”
Section: Discussionsupporting
confidence: 68%
“…Industrial wafers and biscuits presented the highest energy density (approximately 20•9 kJ/g), possibly reflecting a high sugar and fat content (30) , as previously observed in samples of street food in Dushanbe, Tajikistan (26) . Although the free sugar content was not discriminated in this study, they may have a high sugar content, which is line with existing literature on street food composition (10,25,26,31) .…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations